Effect of Polyethylene Glycol Induced Water Stress on Physiological and Biochemical Responses in Pigeonpea (Cajanus cajan L. Millsp.) - G. R. Naik, Ravi Ranjan Kumar, Krishna Karajol and (Recent Research in Science and Technology, 2011)
Water deficit induced by Polyethylene glycol (PEG) affect physiological and biochemical changes in pigeonpea. The plants were subjected to two progressive stresses: moderate (-0.51 MPa) and severe (-1.22 MPa) respectively. The water stress condition was created by irrigating 14 days old grown seedling pot with PEG nutrient solution and decreasing the osmotic potential -0.04 MPa regularly. Relative water content (RWC) content was significantly reduced under water stress condition. Increase in the free proline content during water stress condition suggests that proline is one of the common compatible osmolytes under water stress condition. The genotype exhibited lower accumulation of catalase (CAT) and increased activity of superoxide dismutase (SOD) and Peroxidase (POD) under stressed condition. The present data suggest a relation between proline content and water stress and a well developed antioxidant defense mechanism activated during water stress.